1993
DOI: 10.1007/bf00000445
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of factors controlling the leaching and uptake of inorganic ions in the canopy of a spruce forest

Abstract: Abstract. Sequential sampling of precipitation under mature spruce trees and time-series analysis of the data were performed in order to assess, in natural conditions, the relative importance of different factors that could influence the leaching and uptake of inorganic ions in the canopy. Eleven rain events were analyzed in order to estimate how external factors, rain intensity, H + , and ionic concentration of the incident rain influence the ionic throughfall concentrations and the net throughfall fluxes.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In temperate regions, throughfall solute concentrations at the initiation of events are often high, but constant concentrations late in natural events are not typically reported (Crockford et al 1996;Hambuckers and Remacle 1993;Hansen et al 1994). We assume that constant concentration levels are reached after the complete removal of dry deposition, which requires a critical amount of water (Neary and Gizyn 1994).…”
Section: Throughfall Solute Concentrations and Dynamicsmentioning
confidence: 97%
See 1 more Smart Citation
“…In temperate regions, throughfall solute concentrations at the initiation of events are often high, but constant concentrations late in natural events are not typically reported (Crockford et al 1996;Hambuckers and Remacle 1993;Hansen et al 1994). We assume that constant concentration levels are reached after the complete removal of dry deposition, which requires a critical amount of water (Neary and Gizyn 1994).…”
Section: Throughfall Solute Concentrations and Dynamicsmentioning
confidence: 97%
“…Leaching, which is controlled by nutrient mobility within plants (Hambuckers and Remacle 1993), differed between solutes. In our study, better WS correlation for Mg 2+ than for Ca 2+ with Cl -and K + in throughfall might be explained by faster uptake by roots and transportation within plants for Mg 2+ than for Ca 2+ (Kozlowski and Pallardy 1997).…”
Section: Throughfall Solute Concentrations and Dynamicsmentioning
confidence: 99%
“…Leaching of internal plant pools and ion-exchange processes occurring in the tree canopies contribute to solute enrichment in throughfall (Scherbatskoy and Tyree, 1990;Hambuckers and Remacle, 1993), however, the controls of foliar leaching are still not fully understood. Parker (1983) suggested that fertilisation affects throughfall concentrations by raising the foliar pools of leachable nutrients which has been demonstrated for temperate forest ecosystems (e.g.…”
Section: Canopy Leaching and Uptakementioning
confidence: 99%
“…Parker, 1983;Lovett and Schaefer, 1992;Hambuckers and Remacle, 1993;Hansen et al, 1994;Crockford et al, 1996) only a few studies deal with tropical environments (Stallard and Edmond, 1981;Germer et al, submitted for publication).Within-event throughfall solute concentration dynamics can be highly variable, both between sampling sites and individual events (Parker, 1983). Several authors reported decreasing concentrations that did not reach a constant level during the observation period (Parker, 1983;Hansen et al, 1994), others observed more variable patterns (Hambuckers and Remacle, 1993;Hansen et al, 1994;Crockford et al, 1996). Rainfall intensity is an important control of leaching and wash-off processes (Lovett and Schaefer, 1992;Hansen et al, 1994;Neary and Gizyn, 1994).…”
Section: Introductionmentioning
confidence: 98%